2020
DOI: 10.3846/tede.2020.12736
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Todim Based on Prospect Theory to Select Green Supplier With Q-Rung Orthopair Fuzzy Set

Abstract: Green supply chain has developed rapidly due to the advocacy of ecological civilization, and choosing a proper green supplier is a crucial issue. Considering the fuzziness of evaluation information and the psychological states of decision makers (DMs) in selecting process, a novel TODIM based on prospect theory with q-rung orthopair fuzzy set (q-ROFS) is proposed. The novel TODIM concerns both the perceived transformed probability weighting function and the differences in risk attitudes. A new distance, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…China has paid more and more attention to environmental protection in recent years, as the environmental pollution caused by rapid economic growth has become more serious. Health problems caused by environmental pollution increase health expenditure (47)(48)(49). During the 13th Five-Year Plan period, China has made remarkable achievements in improving environmental quality (50).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…China has paid more and more attention to environmental protection in recent years, as the environmental pollution caused by rapid economic growth has become more serious. Health problems caused by environmental pollution increase health expenditure (47)(48)(49). During the 13th Five-Year Plan period, China has made remarkable achievements in improving environmental quality (50).…”
Section: Research Hypothesesmentioning
confidence: 99%
“…in Reference [13]; p r = 2, = 2 in Reference [18]; k = 1 in Reference [30]; r λ = 6, = (1, 1, 1, 1, 1, 1) in Reference [23]; k = 1 in Reference [25]; r s γ = = 2, = 1 in Reference [21]; k = 1 in Reference [24]; p = 2 in Reference [35]; p θ = 2, = 0.69 in Reference [45]; andθ p = (0.012, 0.025, 0.036, 0.028, 0.043, 0.024), = 1 in Reference [43]. Meanwhile, for the case with group decision, we use the original integrated evaluation matrix and do the corresponding algorithm operation.…”
Section: The Sensitivity Analysis Of Weight Informationmentioning
confidence: 99%
“…Rani and Mishra 44 investigated q‐ ROF weighted aggregated sum product assessment (WASPAS) framework for fuel technology selection. Tian et al 45 presented a revised TODIM based on prospect theory for choosing green supplier under q‐ ROF environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a lot of scholars have devoted to this aspect research and demonstrated the usefulness of behavioral decision-making revealed by the prospect theory (Abdellaoui, 2000;Birnbaum, 2005;Bleichrodt et al, 2009;He & Zhou, 2011;Lu et al, 2020;Zhou et al, 2019). In recent years, prospect theory has been applied to deal with some decision-making problems such as behavioral decision-making (Fan et al, 2013;Wang et al, 2015), multi-attribute decision-making (Fan et al, 2013;Liu et al, 2014;Tian et al, 2018Tian et al, , 2020 and MEDM (Yan & Liu, 2014), etc.…”
Section: Introductionmentioning
confidence: 99%